2018
DOI: 10.1002/hep4.1180
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of the GLOBE and United Kingdom‐primary biliary cholangitis risk scores in a trial cohort of patients with primary biliary cholangitis

Abstract: The GLOBAL Primary Biliary Cholangitis (PBC) Study Group and United Kingdom‐PBC (UK‐PBC) Consortium have demonstrated that dichotomous response criteria are not as accurate as continuous equations at predicting mortality or liver transplantation in PBC. The aim of this analysis was to assess the clinical utility of the GLOBE and UK‐PBC risk scores using data from POISE, a phase 3 trial investigating obeticholic acid (OCA) in patients with PBC. Data (N = 216) at baseline and month 12 were used to calculate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Several studies have validated the ability of Globe and UK-PBC risk scores to predict clinical outcomes in patients with PBC. [41][42][43] Absolute alkaline phosphatase and total bilirubin criteria at 1 year after the UDCA therapy have been used as a more robust predictor of hard endpoints such as liver transplantation or deaths of patients with PBC. 35 More recently, Zhang et al reported that earlier biochemical response to UDCA at 3 or 6 months was devised to identify patients at risk of poor outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have validated the ability of Globe and UK-PBC risk scores to predict clinical outcomes in patients with PBC. [41][42][43] Absolute alkaline phosphatase and total bilirubin criteria at 1 year after the UDCA therapy have been used as a more robust predictor of hard endpoints such as liver transplantation or deaths of patients with PBC. 35 More recently, Zhang et al reported that earlier biochemical response to UDCA at 3 or 6 months was devised to identify patients at risk of poor outcomes.…”
Section: Introductionmentioning
confidence: 99%
“… 6 However, it is showing utility with other treatments as well. 14 , 17 A recent publication quantified the long-term benefit of OCA in the POISE trial through an analysis of data from POISE according to GLOBE score and also the United Kingdom-PBC (UK-PBC) score developed by the UK-PBC Consortium. 14 The GLOBE and UK-PBC scores were also used to assess the benefit of bezafibrate in combination with UDCA in a retrospective cohort of patients from the Japan PBC Study Group.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 17 A recent publication quantified the long-term benefit of OCA in the POISE trial through an analysis of data from POISE according to GLOBE score and also the United Kingdom-PBC (UK-PBC) score developed by the UK-PBC Consortium. 14 The GLOBE and UK-PBC scores were also used to assess the benefit of bezafibrate in combination with UDCA in a retrospective cohort of patients from the Japan PBC Study Group. 17 Both the GLOBE and UK-PBC scores include ALP and total bilirubin, which have been identified as the most important markers in determining LT-free survival in PBC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These easy‐to‐use scores with computer‐aided calculations, allow to continuously quantify the risk for progression over time in a single patient. However, that these scores were solely developed for a patient cohort treated with UDCA monotherapy, and whether these scores based on biochemical responses after 1 year of treatment are also applicable to patients treated with additional drugs such as obeticholic acid (OCA) or bezafibrate should be further validated, although a recent retrospective study suggested that it might be applicable in patient cohorts treated with these drugs . In addition, a UDCA response score able to predict responses to UDCA has been proposed, indicating that higher ALP, higher bilirubin, and lower aminotransferase levels, younger age, longer interval from diagnosis to UDCA treatment, and worsening ALP from diagnosis were associated with a lower probability of UDCA response .…”
Section: Introductionmentioning
confidence: 99%